Amelioration of experimental autoimmune uveoretinitis by inhibition of glyceraldehyde‐derived advanced glycation end‐product formation. Issue 6 (8th September 2014) - Dong, Zhenyu; Iwata, Daiju; Kitaichi, Nobuyoshi; Takeuchi, Masayoshi; Sato, Masashi; Endo, Noriko; Iwabuchi, Kazuya; Ando, Ryo; Fukuhara, Junichi; Kinoshita, Satoshi; Lennikov, Anton; Kitamura, Mizuki; et al.
Abstract : Formation of glyceraldehyde‐derived advanced glycation endoproducts contributes to the pathogenesis of endogenous uvetitis in human and animals. Abstract : AGEs are permanently modified macromolecule derivatives that form through nonenzymatic glycation of amino groups of proteins. Glycer‐AGEs are highly toxic and play an important role in the pathogenesis of chronic inflammatory diseases. However, the contribution of glycer‐AGEs to the pathogenesis of uveitis is unclear. In this study, we measured serum levels of glycer‐AGEs in 100 patients with endogenous uveitis (22 with HLA‐B27‐associated uveitis, 20 with VKH disease, 14 with Behçet's disease, and 44 with sarcoidosis) and 33 healthy volunteers. We then examined the effect of the AGE inhibitor in a mouse model of human endogenous uveitis (EAU) by continuous oral administration of pyridoxamine at 200 or 400 mg/kg/day. Regardless of the etiology, serum glycer‐AGE levels were significantly higher in patients with uveitis than in healthy subjects. Treatment with 400 mg/kg pyridoxamine significantly reduced the clinical and histological severity of EAU and was accompanied by a significant decrease in serum and retinal glycer‐AGE levels and suppression of translocation of NF‐κB p65 into the nucleus of retinal cells. Serum glycer‐AGE levels may therefore serve as a biomarker of human uveitis, as well as systemic inflammation, and may contribute to the progression of uveitis, including diabetic iritis, via the activation of NF‐κB.